Real-World Clinical Outcomes of Manual Versus Powered Endoscopic Staplers in Minimally Invasive Lung Cancer Surgery - Cosimo Lequaglie; Gabriella Giudice; Annalisa Carlucci; Roberto Cascone (Journal of Clinical Medicine, 2026)
Objectives: Manual surgical staplers remain widely used in minimally invasive lung surgery, while powered devices have been introduced to improve tissue compression, staple formation, and device handling. This study compared clinical outcomes associated with manual and powered endoscopic staplers in patients undergoing minimally invasive lung cancer surgery, with postoperative air leak as the main outcome of interest. Methods: We retrospectively reviewed 400 consecutive patients who underwent VATS segmentectomy or lobectomy for lung cancer between January 2023 and June 2025. After 20 exclusions, 380 patients were analyzed: 190 treated with manual staplers (Group A), representing a historical control cohort, and 190 with powered staplers (Group B). Postoperative air leak, operative time, intraoperative blood loss, postoperative complications, and length of stay were compared. Surgeon-perceived ergonomic benefit was assessed after each powered-stapler procedure using a dichotomous yes/no question. Results: Postoperative air leak occurred less frequently with powered than manual staplers (10.0% vs. 17.9%; p = 0.0382; OR = 0.510, 95% CI: 0.279–0.931). No patient developed prolonged air leak (>5 days) or required additional intervention for air leak. Operative time (65.32 ± 2.52 vs. 66.74 ± 3.07 min; p < 0.0001) and intraoperative blood loss (86.09 ± 4.12 vs. 88.3 ± 4.47 mL; p < 0.0001) were statistically lower with powered staplers, although absolute differences were small. No significant differences were observed in postoperative atelectasis or length of stay. All 190 surgeon assessments indicated a perceived ergonomic advantage with the powered stapler. Conclusions: Powered staplers were associated with a lower incidence of postoperative air leak. Operative time and blood loss were also statistically lower, although the absolute differences were of limited clinical relevance and did not translate into shorter hospitalization. Powered staplers were consistently perceived as ergonomically advantageous, although this assessment was subjective and non-validated. These findings warrant cautious interpretation given the retrospective, single-center design and historical-control comparison.